Enhancement of cellulase production in Trichoderma reesei RUT-C30 by comparative genomic screening - Liu, Pei (Microb Cell Fact, 2019)
BACKGROUND: Cellulolytic enzymes produced by the filamentous fungus Trichoderma reesei are commonly used in biomass conversion. The high cost of cellulase is still a significant challenge to commercial biofuel production. Improving cellulase production in T. reesei for application in the cellulosic biorefinery setting is an urgent priority. RESULTS: Trichoderma reesei hyper-cellulolytic mutant SS-II derived from the T. reesei NG14 strain exhibited faster growth rate and more efficient lignocellulosic biomass degradation than those of RUT-C30, another hyper-cellulolytic strain derived from NG14. To identify any genetic changes that occurred in SS-II, we sequenced its genome using Illumina MiSeq. In total, 184 single nucleotide polymorphisms and 40 insertions and deletions were identified. SS-II sequencing revealed 107 novel mutations and a full-length wild-type carbon catabolite repressor 1 gene (cre1). To combine the mutations of RUT-C30 and SS-II, the sequence of one confirmed beneficial mutation in RUT-C30, cre1(96), was introduced in SS-II to replace full-length cre1, forming the mutant SS-II-cre1(96). The total cellulase production of SS-II-cre1(96) was decreased owing to the limited growth of SS-II-cre1(96). In contrast, 57 genes mutated only in SS-II were selected and knocked out in RUT-C30. Of these, 31 were involved in T. reesei growth or cellulase production. Cellulase activity was significantly increased in five deletion strains compared with that in two starter strains, RUT-C30 and SS-II. Cellulase production of T. reesei Δ108642 and Δ56839 was significantly increased by 83.7% and 70.1%, respectively, compared with that of RUT-C30. The amount of glucose released from pretreated corn stover hydrolyzed by the crude enzyme from Δ108642 increased by 11.9%. CONCLUSIONS: The positive attribute confirmed in one cellulase hyper-producing strain does not always work efficiently in another cellulase hyper-producing strain, owing to the differences in genetic background. Genome re-sequencing revealed novel mutations that might affect cellulase production and other pathways indirectly related to cellulase formation. Our strategy of combining the mutations of two strains successfully identified a number of interesting phenotypes associated with cellulase production. These findings will contribute to the creation of a gene library that can be used to investigate the involvement of various genes in the regulation of cellulase production. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-019-1131-z) contains supplementary material, which is available to authorized users.